Evidences of the Low Implication of Mosquitoes in the Transmission of Mycobacterium ulcerans, the Causative Agent of Buruli Ulcer - Rousseau Djouaka; Francis Zeukeng; Jude Daiga Bigoga; David N’golo Coulibaly; Genevieve Tchigossou; Romaric Akoton; Sylla Aboubacar; Sodjinin Jean-Eudes Tchebe; Clavella Nantcho Nguepdjo; Razack Adeoti; Innocent Djegbe; Manuele Tamo; et al. (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Buruli ulcer (BU) continues to be a serious public health threat in wet tropical regions and the mode of transmission of its etiological agent, Mycobacterium ulcerans (MU), remains poorly understood. In this study, mosquito species collected in endemic villages in Benin were screened for the presence of MU. In addition, the ability of mosquitoes larvae to pick up MU from their environment and remain colonized through the larval developmental stages to the adult stage was investigated. Methods. 7,218 adults and larvae mosquitoes were sampled from endemic and nonendemic villages and screened for MU DNA targets (IS2404, IS2606, and KR-B) using qPCR. Results. MU was not detected in any of the field collected samples. Additional studies of artificially infected larvae of Anopheles kisumu with MU strains revealed that mosquitoes larvae are able to ingest and host MU during L1, L2, L3, and L4 developmental stages. However, we noticed an absence of these bacteria at both pupae and adult stages, certainly revealing the low ability of infected or colonized mosquitoes to vertically transmit MU to their offspring. Conclusion. The overall findings highlight the low implication of mosquitoes as biological vectors in the transmission cycle of MU from the risk environments to humans.